The City and its Environment: Competition and/or Co-operation? (A Hungarian Case Study) - Szirmai, Viktória; A. Gergely, András; Baráth, Gabriella; Molnár, Balázs; Szépvölgyi, Ákos (Discussion Papers, 2012)
During the East Central European changes starting from 1989 there was a sharp competition among Hungarian settlements as well for winning grants to ease the outcomes of their economic crisis and to get venture capital support, for the attraction of external foreign investors, for the chances of integration into international, local and regional networks and for the chances of their quick economic development. This paper is a shortened version of the book 'Competition and/or Co-operation? Relations between the City and Its Environment' published by the Sociological Research Institute of HAS and Centre for Regional Studies HAS in 2002. The research was carried out within the framework of PICS (Programme Internationale de Coopération Scientifique). The aim of the research was the exploration of regional and urban development processes in indus¬trial cities and their environment in Hungary’s regions of diverse economic devel¬opment, the relations between cities and their environment and the sociological factors, interests and social conflicts having a major role in the estab¬lishment of co-operation. The research was also exploring the attitude of economic and social actors towards urban development and competition policies.